The Śāriputra and Raudrākṣa – On the Identity of the Bronze Drum in the Dunhuang Murals - Minqian Liao (Távol-keleti Tanulmányok)
The story of Śāriputra and Raudrākṣa (Laoducha shengdou bian 勞度叉聖鬥變) involves Minister Sudatta’s encounter with the Buddha while seeking a bride for his son. Sudatta’s conversion leads to the construction of a monastery, sparking a contest between Buddhist monks and six sectarian teachers, with Śāriputra’s victory over Raudrākṣa showcasing Buddhist supremacy. The Dunhuang murals, based on the Xiangmo bianwen 降魔變文 (The Demon Conquering Story), are derived from the Buddhist Xian yu jing 賢愚經 (Sūtra of the Wise and the Foolish) and reflect a complex relationship between scripture, bianwen 變文, and the murals. This article explores how these forms differ while maintaining a connection, focusing on the dharma combat scenes and the symbolic use of dharma instruments. The cross-patterned jin drum (jin gu 金鼓) in the contest between Śāriputra and Raudrākṣa is a fascinating element embedded in the broader context of Dunhuang murals, manuscripts, and the religious and cultural symbolism of late Tang dynasty art. The article inquiry into the interpretation of the jin drum, its identity, and the significance of the cross pattern involves a detailed examination of archaeological, artistic, and textual evidence.